LEGAL PROTECTION OF CREDITORS IN THE DISSOLUTION OF LIMITED LIABILITY COMPANIES WITHOUT LIQUIDATION: AN ANALYSIS OF THE PIERCING THE CORPORATE VEIL DOCTRINE - Angelica Brigitta Michelle Rusli; Caitlyn Nadya Aurelia; Jesslyne Burhan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The dissolution of a Limited Liability Company (PT) without undergoing proper liquidation procedures constitutes an abuse of legal entity status that is detrimental to creditors. This practice is often employed as a means to evade contractual obligations, which normatively contradicts the principles of good corporate governance. This study aims to examine the limits of liability of corporate organs in the liquidation process and to analyze the relevance of the Piercing the Corporate Veil (PTCV) doctrine as an extraordinary legal remedy for creditors. The research method used is normative juridical with a descriptive-analytical specification. The primary data sources include Law Number 40 of 2007 concerning Limited Liability Companies and its implementing regulations within the SABH system of the Ministry of Law and Human Rights. The findings indicate that the dissolution of a company without the settlement of debts constitutes an ultra vires act that nullifies the protection of limited liability. The PTCV doctrine allows judges to disregard the company’s legal entity status and impose joint and several liability on Directors or Shareholders personally if elements of bad faith are proven. This study underscores the urgency of synchronizing the electronic registration system with liquidation oversight mechanisms to minimize the unilateral and irresponsible removal of legal entity status.